2024
DOI: 10.2147/idr.s445243
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Risk Factors for Death in Critically Ill Patients with Carbapenem-Resistant Klebsiella pneumoniae Treated with Ceftazidime-Avibactam: A Retrospective Study

Lingchun Zhang,
Yani Ma,
Chenglong Zhao
et al.

Abstract: Purpose Carbapenem-Resistant Klebsiella pneumoniae (CRKP) is a significant public health threat, because it is associated with substantial morbidity and mortality. However, the risk factors associated with treatment failure of ceftazidime-avibactam (CAZ-AVI) and the need for CAZ-AVI-based combination remain unclear. Methods We conducted a retrospective study of critically ill patients (age: > 18 years) diagnosed with CRKP infections and treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…reported 38.1% 30-day mortality in the liver transplant population, which was significantly higher than the 30-day mortality in our study (19.4%), which could be attributed to the difference in patient severity between studies. Our study revealed that 30-day mortality was associated with higher APACHE II scores, consistent with previous reports ( Zhang et al., 2024 ). A meta-analysis conducted by Qian et al ( Qian et al., 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…reported 38.1% 30-day mortality in the liver transplant population, which was significantly higher than the 30-day mortality in our study (19.4%), which could be attributed to the difference in patient severity between studies. Our study revealed that 30-day mortality was associated with higher APACHE II scores, consistent with previous reports ( Zhang et al., 2024 ). A meta-analysis conducted by Qian et al ( Qian et al., 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although some studies have indicated that CAZ-AVI treatment for CR-GNB infections is more effective than polymyxins and tigecycline (van Duin et al, 2018;Fang et al, 2021;Shi et al, 2021), the risk factors associated with treatment failure of CAZ-AVI remain unclear, especially in this special population of KT recipients. Additionally, previous in vitro studies have demonstrated that CAZ-AVI, when used in combination with other drugs, exhibits high synergistic activity against CR-GNB (Gaibani et al, 2017;Wang et al, 2021;Zhang et al, 2024). However, it is unclear whether this combination is beneficial.…”
Section: Introductionmentioning
confidence: 99%